O lixo visto sob uma outra ótica jurídica - Maia Filho, Roberto (2005)
ABSTRACT In this paper, garbage legal aspects nowadays are analysed under the influence and rules of diffuse and specially environmental law. As unisonal doctrine denies environmental heritage as res nullius (nobody s property) and qualifies it as res communes ommium (everybody s property), garbage is not supposed to be considered anymore as a mere res derelictae (abandoned property), turning out to be also a kind of obligatio communes ommium (an obligation or problem concerning everyone), due to the social relevance within the present circumstances. Over population, inordinated growth of towns and consumption, in short, aggravation of environmental problems, as further analysed, justifies a special attention towards the subject and a deeper analysis of legal aspects involved in this matter. That s what this scientific work was meant for dealing with a matter not much explored by jurists, with a deep conviction that, unless we join our efforts to look for solutions concerning solid waste, properly ruling its destination, life will be seriously threatened in its preservation and maintenance.